P166 Quantiferon testing in close contacts of smear positive pulmonary TB identifies people at low risk of secondary progression. (16th November 2010) - Haldar, P; Thuraisingam, H; Patel, H; Hoskyns, W; Woltmann, G
Abstract : Introduction: Interferon gamma release assays (IGRAs) are recommended for screening close contacts of patients with active tuberculosis (TB) in the UK. Compared with tuberculin skin testing, greater specificity with IGRAs reliably informs the need for chemoprophylaxis in screened contacts by identifying latent Mycobacterium tuberculosis infection (LTBI) associated with a high risk of secondary disease progression. However, the risk of secondary progression varies with the nature of disease in the primary case and is greatest for contacts of smear positive pulmonary disease. The role of IGRAs in this very high risk population is not clear. Aim: To evaluate the benefit of screening with QuantiFERON ® -TB Gold (QFT) in contacts of smear positive pulmonary TB. Methods: A prospective observational study. We have offered QFT based single step screening programme for all close contacts of smear positive pulmonary TB since January 2007. We present 2-year follow-up data in tested and untested contacts that did not receive chemoprophylaxis. Secondary disease risk is estimated with Kaplan–Meier analysis and subgroups compared with the log-rank test. Results: 576 recorded contacts for 92 smear positive cases. Median follow-up 693 days (range 287–1146 days). 467 (81.1%) of contacts were QFT screened. 36% of tested contacts had a positive QFT; 83 QFT positive contacts did not receive chemoprophylaxis (group A); 101 contacts were not screened and untreated (group B); 301 were QFT negative (group C). Secondary disease occurred in 22 contacts (11 group A, 5 group B). Progression rates at 12 and 24 months are shown (Abstract P166 Table 1 ). Compared with the untested subgroup, a positive QFT results did not significantly increase progression risk (RR 2.1 (95% CI 0.7 to 5.9), p=0.13). A negative QFT result did significantly lower progression risk (RR 0.28 (95% CI 0.09 to 0.82) at 2 years, p=0.01). The negative predictive value of QFT compared with not testing was 93.2% (95% CI 85.8 to 97.5). Conclusion: In contrast with other TB disease types, QFT screening in contacts of smear positive pulmonary TB does not identify contacts for chemoprophylaxis, but rather identifies contacts that we may choose not to treat.